Analisis Swot Sebagai Landasan Dalam Menentukan Strategi Pemasaran Oleh Two Mart Swalayan - Ahmad Vajri Rahman; nofritar nofritar (Riset Sinergi Indonesia, 2022)
This research was conducted at Two Mart Swalayan which is a business engaged in the retail sector in the city of Padang, the background underlying this research is the unstable sales problem experienced by Two Mart Swalayan in the last 2 years which tends to fall slightly in the middle. in the last year, so an analysis is needed to identify the causes of the problem and the right marketing strategy is needed to overcome it. The method used is a SWOT analysis with IFAS and EFAS matrices and a cartesian diagram of SWOT analysis.The results showed that the position of Two Mart Swalayan is in quadrant II because it has the highest strategy score SO = 5.361, followed by other strategy scores SO = 4.973, WT = 3.302 and WO = 2.914. In this condition, the suitable marketing strategy to use is ST (Strength - Threats), which is a diversification strategy, where this diversification strategy is a way to manage risks by minimizing potential hazards by exploiting existing opportunities. Diversification strategies that can be used are such as horizontal diversification, namely adding non-existing products and providing new services with the use of technology so as to make customers more interested in shopping at Two Mart Swalayan